Uskonto, kieli ja yhteiskunta Johdatus diskursiiviseen uskonnontutkimukseen - Hjelm, Titus (Tietolipas, 2021)
Discursive study of religion (DSR) has become an increasingly recognised and applied approach to the study of religion. It asks: What passes for 'religion' in society? How do different constructions of 'religion' affect other social spheres such as politics, law, and everyday life, and vice versa? In this collection, Finnish scholars-many of them internationally recognized authorities on the subject-discuss DSR's theoretical underpinnings, map the variety of discursive approaches, and apply the approach to case studies of politics, spirituality, and history. The book can be used as a textbook for religion and method courses in various disciplines.